Integrated utilization of land and vegetation in secondary forest areas - Asep Suheri; Rina W. Cahyani; Asef K. Hardjana; Endah Sulistyawati (3BIO: Journal of Biological Science, Technology and Management, 2019)
Local community's activities around Labanan forest area for specific purposes already make the area unsafe. Responding to this, land productivity optimization with agroforestry patterns might be applied in the area. Hopefully, through these systems, utilization and productivity of natural forests in Labanan forest area might be optimized in producing food, energy and water conservation, outside its regular function as forestry area. The purpose of this study was to determine the condition of the land under treeing forest; generate analytical data of vegetation in the research plots; and determine carbon stocks undergrowth. The research method was soil sampling, vegetation analyzes and sampling of undergrowth plant biomass. Based on laboratory analysis result, soil pH ranging between 5-7, N Total <0.3%, P Total <49 mg P2O5.100g-1, K Total between 2-8 mg K2O.100g-1, and the organic carbon content on soil <2.1%. The vegetations dominated by cunday (Saraca declinata) as many as 43 trees/ha with basal area 21.55 m2. ha-1. The highest important value index (IVI) shown by the type of vegetation cunday (Saraca declinata) amounted to 51.43% and the lowest was shown by bintangur (Callophyllum sp) amounted to 2.89%. Stock carbon undergrowth on research area ranged from 1.470 to 1.752ton C. ha-1.